تأثیر بعض القد ا رت البدنیة والحركیة باستخدام أدوات مساعدة وإنجاز فعالیة رمي الرمح - ابتسام حيدر بكتاش (physical education and sport sciences college for women/ Baghdad University, 2016)
This study aimed to identify the impact of exercises designed in some physical and motor abilities using utilities and completion of the effectiveness of the javelin throw, the researcher used the experimental method for suitability and the nature of the research, which included research sample (52) students from the first year for the academic year 2013/2014, divided evenly into two groups. (experimental and control group), as the experimental group used some utilities designed by the researcher (shaft tool weights, different sizes and animation tool roller medical and balls), while the control group based on the usual way of learning and training It was conducted homogeneity and parity between the two groups in some age, height and weight variables and some elements of physical fitness , and took the approach (4) weeks and by (2) educational unit - training each week and was the unit time ( 90 minutes) , as used some statistical treatments to reach the result ( arithmetic mean, standard deviation, Law (t.test) for comparison between the two groups ) . The researcher found the results there has been a clear evolution of ratios between the two groups through the use of various tools to help in the development of physical and motor abilities accomplish javelin .